2016
DOI: 10.1080/15384047.2016.1139267
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-CDK inhibitor P1446A-05 restricts melanoma growth and produces synergistic effects in combination with MAPK pathway inhibitors

Abstract: Nearly 100% of melanomas have a defect in the p16 INK4A:cyclin D-CDK4/6:RB pathway, leading to abnormal cell cycle control and unregulated cellular proliferation. Here, we report that P1446A-05, a novel multi-CDK inhibitor has significant inhibitory activity against cutaneous and uveal melanoma. Mechanistic studies revealed that P1446A-05 inhibits phosphorylation targets of CDK members, and induces cell cycle arrest and apoptosis irrespective of melanoma genotype or phenotype. Additionally, we show preclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Voruciclib, a CDK4/6 inhibitor, has shown promising anti-cancer effects in combination with the BRAF inhibitor, vemurafenib in advanced BRAF-mutant melanoma [17]. More recent studies have shown that voruciclib enhances the sensitivity of the proteasome inhibitor, bortezomib, in triple negative breast cancer xenografts [18]. However, there is no published data indicating the sensitizing effects of voruciclib in cells overexpressing ABC transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Voruciclib, a CDK4/6 inhibitor, has shown promising anti-cancer effects in combination with the BRAF inhibitor, vemurafenib in advanced BRAF-mutant melanoma [17]. More recent studies have shown that voruciclib enhances the sensitivity of the proteasome inhibitor, bortezomib, in triple negative breast cancer xenografts [18]. However, there is no published data indicating the sensitizing effects of voruciclib in cells overexpressing ABC transporters.…”
Section: Introductionmentioning
confidence: 99%
“…It displays potent antiproliferative activity across 30 cancer cell lines, including prostate, colon, and lung cancer cells 215 . It displays synergistic activity with dabrafenib and trametinib in A375 and K4 cell lines 213 . In two phase I studies in patients with advanced refractory tumors, it has shown acceptable safety profile 217,218 .…”
Section: Cdk Inhibitors In Clinical and Preclinical Pipelinementioning
confidence: 99%
“…Voruciclib (P1446A-05, 73) is a structural analog of P276-00 that inhibits CDK9 (IC 50 = 22 nM) and is orally bioavailable. [213][214][215][216] It displays potent antiproliferative activity across 30 cancer cell lines, including prostate, colon, and lung cancer cells. 215 It displays synergistic activity with dabrafenib and trametinib in A375 and K4 cell lines.…”
Section: Aminopyridinesmentioning
confidence: 99%
See 2 more Smart Citations